Unveiling Growth Patterns and Condition Status of 25 Flatfish Species (Order: Pleuronectiformes) from the Southern Coast of Tamil Nadu, India: Evidence from Length–Weight Relationships - R. G. Sasikumar; P. Jawahar; N. Jayakumar; G. Arul Oli; T. Ravikumar; M. Sharumathi; J. Joyson Paul; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Hybrid AI-IoT-Blockchain frameworks for energy-efficient smart homes: a multidimensional review of technologies, policies, and socioeconomic implications - G. Gulothungan; T. Raja; Yuvarajan Devarajan; Mahit Jain; Honganur Raju Manjunath; Md Asif; M. Madhusudhan; Satish Choudhury; Ravikumar Jayabal (Energy and Buildings, 2026)

Deciphering Environmental Drivers on Plankton Dynamics in Punnakayal–Pazhayakayal Estuarine Complex, Southern Coast of India - Kamei Ringjonmeilu; N. Jayakumar; R. Durairaja; V. Rani; T. Ravikumar; R. Saravanan; C. Sudhan; Adyasha Sahu; J. Joyson Paul; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Comparative Assessment of Length-Weight Relationship and Relative Condition Factor of 25 Grouper Species along the Southern Coast of Tamil Nadu, India - J. Joyson Paul; R. Durairaja; N. Jayakumar; N. Daniel; T. Ravikumar; M. Sharumathi; R. G. Sasikumar; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Ecological risk and source attribution of macro litter in the biodiverse blue carbon mangrove ecosystem along the Gulf of Mannar - Muthu Ponmani; P. Padmavathy; D. Manimekalai; R. Shalini; T. Ravikumar; G. Hariharan; S. Manickavasagam (Marine Pollution Bulletin, 2026)

Characterization of microbial diversity in the harbour and ballast water of ships in the Gulf of Mannar, India using environmental DNA - S. Sangeetha; A. Pavan-Kumar; J. Robina; T. RaviKumar; G. Iqbal; P. Bipul; H. Sanath Kumar; P. Krishnan; A. Chaudhari (Regional Studies in Marine Science, 2025)

Spatial variation and pollution indices of anthropogenic marine litter on the beaches in gulf of Mannar, India - Muthu Ponmani; P. Padmavathy; D. Manimekalai; R. Shalini; T. Ravikumar; G. Hariharan (Marine Pollution Bulletin, 2025)

Enhancing marine diesel engine compatibility with sustainable fuels: Key factors and adjustments - Christopher Selvam Damian; Yuvarajan Devarajan; Ravikumar Jayabal; T. Raja (Marine Pollution Bulletin, 2025)

Vulnerability of mangrove ecosystems to anthropogenic marine litter along the southeast coast of India - Muthu Ponmani; P. Padmavathy; D. Manimekalai; R. Shalini; T. Ravikumar; G. Hariharan; S. Manickavasagam (Science of The Total Environment, 2024)

A comprehensive review of biomass pyrolysis for hydrogen production in India - Christopher Selvam Damian; Yuvarajan Devarajan; T. Raja; Ravikumar Jayabal (Process Safety and Environmental Protection, 2024)

Brown-top millet: an overview of breeding, genetic, and genomic resources development for crop improvement - P. Bhavani; C. Nandini; Theivanayagam Maharajan; T. M. Ningaraju; B. Nandini; S. Gazala Parveen; K. Pushpa; R. L. Ravikumar; T. E. Nagaraja; Stanislaus Antony Ceasar (Planta, 2024)

Design, synthesis, and biochemical and computational screening of novel oxindole derivatives as inhibitors of Aurora A kinase and SARS-CoV-2 spike/host ACE2 interaction - Donatus B. Eni; Joel Cassel; Cyril T. Namba-Nzanguim; Conrad V. Simoben; Ian Tietjen; Ravikumar Akunuri; Joseph M. Salvino; Fidele Ntie-Kang (Medicinal Chemistry Research, 2024)
Isatin (indol-2,3-dione), a secondary metabolite of tryptophan, has been used as the core structure to design several compounds that have been tested and identified as potent inhibitors of apoptosis, potential antitumor agents, anticonvulsants, and antiviral agents. In this work, several analogs of isatin hybrids have been synthesized and characterized, and their activities were established as inhibitors of both Aurora A kinase and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike/host angiotensin-converting enzyme II (ACE2) interactions. Amongst the synthesized isatin hybrids, compounds 6a , 6f , 6g , and 6m exhibited Aurora A kinase inhibitory activities (with IC 50 values < 5 $$μ$$ μ M), with GScore values of −7.9, −7.6, −8.2 and −7.7 kcal/mol, respectively. Compounds 6g and 6i showed activities in blocking SARS-CoV-2 spike/ACE2 binding (with IC 50 values in the range < 30 $$μ$$ μ M), with GScore values of −6.4 and −6.6 kcal/mol, respectively. Compounds 6f , 6g , and 6i were both capable of inhibiting spike/ACE2 binding and blocking Aurora A kinase. Pharmacophore profiling indicated that compound 6g tightly fits Aurora A kinase and SARS-CoV-2 pharmacophores, while 6d fits SARS-CoV-2 and 6l fits Aurora A kinase pharmacophore. This work is a proof of concept that some existing cancer drugs may possess antiviral properties. Molecular modeling showed that the active compound for each protein adopted different binding modes, hence interacting with a different set of amino acid residues in the binding site. The weaker activities against spike/ACE2 could be explained by the small sizes of the ligands that fail to address the important interactions for binding to the ACE2 receptor site.

Exploring the potential of sulphur forms in Northeastern Indian coals: Implications in environmental remediation and heavy metal sensing - Manabendra Nath; P. Gopinathan; M.S. Santosh; T. Subramani; Vallu Ramakrishna; Afaq Ahmad Khan; C.R. Ravikumar (Chemosphere, 2023)

Estimation of urea reaction rate constants in paddy fields - S. Vanitha; V. Ravikumar; T. Sherene Jenita Rajammal (Paddy and Water Environment, 2023)

Remote sensing based agricultural drought assessment in Palar basin of Tamil Nadu state, India - T. Murali Krishna; G. Ravikumar; M. Krishnaveni (Journal of the Indian Society of Remote Sensing, 2009)

Sporophytic and gametophytic recurrent selection for improvement of partial resistance to Alternaria leaf blight in sunflower (Helianthus annuus L.) - Shobha Rani T.; R. L. Ravikumar (Euphytica, 2006)

Use of egg yolk in seromonitoring against newcastle disease - Parimal Roy; S. Anandan; G. Ravikumar; A. Koteeswaran; A. T. Venugopalan (Tropical Animal Health and Production, 1997)